Word retrieval in aphasia: From naming tests to connected speech and the impact on well-being. - Biran, Michal; Ben-Or, Galit; Yihye-Shmuel, Hila (Aphasiology, 2024)
Language assessment includes mainly structured tasks; however, everyday communication requires additional abilities. An important clinical question is whether the performance of individuals on structured language tasks can predict their performance and participation in everyday communication, and how it affects their well-being. We aimed to examine whether the performance on structured tests represents individuals' participation in everyday communication, focusing on lexical retrieval and comparing structured tasks and less structured tasks. In addition, we examined whether the performance on these measures is compatible with individuals' self-report on a questionnaire. Twenty people with aphasia (PWA. Mean age: 61 years; mean months post-onset: 42), with comprehension and cognition abilities that enabled understanding and performing the tasks participated in the study. They were administered tasks of single word retrieval (picture naming) and word retrieval in connected speech: story-telling and conversation on initiated topic. In addition, the Aphasia Impact Questionnaire-21 (AIQ-21. Swinburn et al., 2019) was administered, a pictorial self-report questionnaire adapted for PWA which evaluates communication, participation, and well-being. Connected speech was assessed using two measures: (a) the %WR (Percent Word Retrieval; Mayer & Murray, 2003), calculating the percent of correctly produced nouns and verbs and (b) the Measure of Participation in Conversation (MPC. Kagan et al., 2004). (a) Nouns were retrieved significantly better in conversation compared to picture naming and story-telling; (b) Moderate correlations were found between word retrieval in the picture naming task and the less structured tasks (story-telling and conversation); (c) Scores in the self-report questionnaire and specifically in the well-being section were correlated with success in word retrieval in connected speech as well as with the MPC measure. The results indicate that performance in a picture naming task differs from retrieval in connected speech. Thus, it is important to include connected speech tasks in language assessment of PWA to better evaluate the ability to participate in everyday conversation. Furthermore, a self-report questionnaire adds information for assigning treatment goals.